Diagnostic inertia in obesity and the impact on cardiovascular risk in primary care: a cross-sectional study - Martínez-St John, Damian RJ (Br J Gen Pract, 2015)
BACKGROUND: Prevalence of diagnostic inertia (DI), defined as a failure to diagnose disease, has not been analysed in patients with obesity. AIM: To quantify DI for cardiovascular risk factors (CVRF) in patients with obesity, and determine its association with the cardiovascular risk score. DESIGN AND SETTING: Cross-sectional study of people ≥40 years attending a preventive programme in primary healthcare centres in Spain in 2003–2004. METHOD: All patients with obesity attending during the first 6 months of the preventive programme were analysed. Participants had to be free of CVD (myocardial ischaemia or stroke) and aged 40–65 years; the criteria used to measure SCORE (Systematic COronary Risk Evaluation). Three subgroups of patients with obesity with no personal history of CVRF but with poor control of risk factors were established. Outcome variable was DI, defined as poor control of risk factors and no action taken by the physician. Secondary variables were diabetes, fasting blood glucose (FBG), body mass index (BMI), and SCORE. Adjusted odds ratios (OR) was determined using multivariate logistic regression models. RESULTS: Of 8687 patients with obesity in the programme, 6230 fulfilled SCORE criteria. Prevalence of DI in the three subgroups was: hypertension, 1275/1816 (70.2%) patients affected (95% CI = 68.1 to 72.3%); diabetes, 335/359 (93.3%) patients affected (95% CI = 90.7 to 95.9%); dyslipidaemia subgroup, 1796/3341 (53.8%) patients affected (95% CI = 52.1 to 55.4%. Factors associated with DI for each subgroup were: for hypertension, absence of diabetes, higher BMI, and greater cardiovascular risk; for dyslipidaemia, diabetes, higher BMI, and greater cardiovascular risk (SCORE); and for diabetes, lower FBG levels, lower BMI, and greater cardiovascular risk. CONCLUSION: This study quantified DI in patients with obesity and determined that it was associated with a greater cardiovascular risk.